PENGARUH PEMASARAN DIGITAL DAN PEMASARAN HUBUNGAN PELANGGAN TERHADAP LOYALITAS PELANGGAN WILL FITNESS KELAPA GADING JAKARTA UTARA - Rosdiana; Julnifer Sitorus (Jurnal Ekonomi dan Industri, 2024)
The analyze the influence of digital marketing and customer relationship marketing on Customer Loyalty at Will Fitness Kelapa Gading, North Jakarta. This research is included in the category of causal associative research using a quantitative approach. The population in this study were members of Will Fitness Kelapa Gading, North Jakarta. The technique used for sampling was simple random sampling, using the Slovin formula. The analytical method uses simultaneous and partially linear regression analysis. The research results show that in simultaneous digital marketing and customer relationship marketing have a significant effect on customer loyalty at Will Fitness Kelapa Gading, North Jakarta. In partially terms, digital marketing has a positive and significant effect on customer loyalty. Customer relationship marketing has a positive and significant effect on customer loyalty.